Oxytocin Enhances the Neural Efficiency of Social Perception - Tillman, Rachael; Gordon, Ilanit; Naples, Adam; Rolison, Max; Leckman, James F.; Feldman, Ruth; Pelphrey, Kevin A.; McPartland, James C. (Frontiers in Human Neuroscience, 2019)
Face perception is a highly conserved process that directs our attention from infancy and is supported by specialized neural circuitry. Oxytocin can increase accuracy and detection of emotional faces, but these effects are mediated by valence, individual differences, and context. We investigated the temporal dynamics of oxytocin’s influence on the neural substrates of face perception using event related potentials (ERP). In a double blind, placebo controlled within-subject design, 21 healthy male adults inhaled oxytocin or placebo and underwent ERP imaging during two face processing tasks. Experiment 1 investigated effects of oxytocin on neural correlates of fearful versus neutral facial expressions, and Experiment 2 manipulated point-of-gaze to neutral faces. In Experiment 1, we found that oxytocin reduced N170 latency to fearful faces. In Experiment 2, N170 latency was decreased when participant gaze was directed to the eyes of neutral faces; however, there were no oxytocin-associated effects in response to different facial features. Findings suggest oxytocin modulates early stages of social perception for socially complex information such as emotional faces relative to neutral. These results are consistent with models suggesting oxytocin impacts the salience of socially informative cues during processing, which leads to downstream effects in behavior. Future work should examine how oxytocin affects neural processes underlying basic components of social behavior (such as, face perception) while varying emotional expression of stimuli or comparing different characteristics of participants (e.g., gender, personality traits).